Rethinking Populist Discourse from Latin America: Algorithmic Activism and the Constitution of a People in Chile - Bonnin, Juan Eduardo (2020)
The aim of this article is to explore some of the ideological and empirical limits of studies on populism from a perspective based on Latin American history and theories, on one hand, and current ideas about digitalization and political discourse, on the other. I will first argue that studies on populism have a monolingual bias that conceals an ethnocentric view on academic research. As a consequence, when the term “populism” is applied to Latin American political discourse and history, it implies a pejorative view on democracies other than liberal European. Leaving aside this perspective, I will then present a different view of Latin American populisms, which allows for a richer, more complex perspective, including the key role of “the people” as a discursive actor that can even dispense with a populist leader, especially in the case of mediatized democracies. As a case study, I will analyze activism in Chile by observing Twitter’s Trending Topics (TT) during the first week of the mass protests in October 2019. The analysis of TT hashtags helped us to better desccribe this process as one of handcrafted algorithmic activism which developed at least four tactics: the formulation of explicit demands, off-hours tweetstorms, syntagmatic variation, and HT confrontation and appropriation.